2023
DOI: 10.5093/pi2023a3
|View full text |Cite
|
Sign up to set email alerts
|

Women Victims of Intimate Partner Violence and Intimate Partner Homicide: A Typology Based on Victimization Variables

Abstract: Intimate partner violence against women (IPVAW) and intimate partner homicide against women (IPHAW) are multidimensional phenomena. The aim of this study was to identify typologies of Spanish IPHAW and IPVAW victims, based on the differences between their characteristics and the determinants of aggression. The sample consisted of 381 cases from the Spanish Integral Monitoring System in Cases of Gender Violence. The instrument used was a semistructured interview. Results showed differences between IPHAW and IPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…Even though the profile and characteristics of the victimized and revictimized women were quite similar, it was identified that, as suggested by previous literature, women who experience greater economic precariousness, social isolation, and have children are those at higher risk of revictimization ( Cheng & Lo, 2015 ; Katerndahl, et al, 2013 ; Pineda et al, 2023 ). These data confirm that the chronic victimization of these women often forms part of a broader reality characterized by disadvantage and widespread social exclusion.…”
Section: Discussionmentioning
confidence: 78%
“…Even though the profile and characteristics of the victimized and revictimized women were quite similar, it was identified that, as suggested by previous literature, women who experience greater economic precariousness, social isolation, and have children are those at higher risk of revictimization ( Cheng & Lo, 2015 ; Katerndahl, et al, 2013 ; Pineda et al, 2023 ). These data confirm that the chronic victimization of these women often forms part of a broader reality characterized by disadvantage and widespread social exclusion.…”
Section: Discussionmentioning
confidence: 78%
“…The present study seeks to explore the differences in personality between lethal IPVAW perpetrators and non-lethal ones to deeply understand this risk factor at an individual level what makes someone commit homicide or aggression. Also, understanding IPVAW from a dyadic approach (Leone et al, 2016 ; Sommer et al, 2017 ), we aim to explore the differences between these perpetrator personalities and their victims and between both groups of victims as has been done in previous studies with other different characteristics of these populations (e.g., Pineda, Galán, et al, 2023 ; Pineda, Rico-Bordera, et al, 2023 ). Furthermore, due to its usefulness in this applied field, we aim to add research to the interpersonal accuracy field, by testing the accuracy of trained judges in assessing personality indirectly in non-laboratory conditions.…”
Section: The Present Studymentioning
confidence: 99%
“…A second limitation is related to the correlational methods. Since the groups, although similar, were not matched attending to different sociodemographic variables, thus the personality differences might have been affected by variables like the number of stressors at the time of the events, lack of support from the perpetrator, or other variables that differentiate these groups (for more information about these differences, see Pineda, Galán, et al, 2023 ; Pineda, Rico-Bordera, et al, 2023 ).…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Por su parte, Berk et al (2021) proporcionan un examen integrado de la equidad y precisión en las evaluaciones de riesgos de la justicia penal a partir de la revisión de la literatura existente en criminología, informática y estadística. Con el mismo propósito de diseñar instrumentos más específicos y eficaces para la evaluación del riesgo cabe mencionar los trabajos centrados en el refinamiento de las tipologías de las víctimas de violencia de género (Pineda et al, 2023;Vignola-Lévesque y Léveillée, 2022;Santos et al, 2022).…”
Section: Introductionunclassified